Cultural influences on the law of the sea : history, legacy, and future prospects - Kraska, James; Ryou-Ellison, Hayoun (Oxford : Oxford University Press, 2025)
This book explores the cultural norms that underpin oceans governance, from the regulation of maritime shipping to seabed mining and the protection of the marine environment. The great cultural norms of the world's major civilizations have informed and continue to shape international maritime law. These norms or values include freedom and liberty emanating from Western Europe, Latin American cultural concepts of dependency theory and post-colonial security, African notions of community and common heritage, and the East Asian belief in Confucian social hierarchy. While fortune is often geography, policy preferences and international diplomacy are also shaped by enduring cultural norms and values. This volume analyses the contributions of regional cultures to the international law of the sea, from historic development to contemporary practice. The continental-sized civilizations in this volume cover Western Europe, Eastern Europe, North America, Latin America, Africa, South Asia, East Asia, and Oceania. In assessing the influences of these cultural regions, the book concludes with a normative evaluation of what each of the world's civilizations has contributed to the law of the sea and how they can promote oceans governance today
BIBINDX
Specialized
Keywords: Law of the sea -- History